2020
DOI: 10.1111/jfbc.13189
|View full text |Cite
|
Sign up to set email alerts
|

Improved antioxidant and immunomodulatory activities of enzymatically degraded Porphyra haitanensis polysaccharides

Abstract: Porphyra haitanensis polysaccharide (CPH) was degraded by pectinase to improve its biological activities. Box–Behnken response surface design was used to optimize the hydrolysis conditions. The molecular weight of CPH and the degraded P. haitanensis polysaccharide (DCPH) were measured to be 524 and 217 kDa, respectively. GC–MS spectrometry results showed that CPH and DCPH were mainly composed of galactose. In vitro antioxidant assays indicated that DCPH possessed improved radical scavenging activity and ferric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…After 24 h incubation, ESFP1, ESFP2 and ESFP3 displayed an appreciable effect on promoting the RAW264.7 cell proliferation ( Figure 6 a ) in a similar fashion to that reported by other researchers [21,22] . Such effect enhanced first and then reduced with increasing concentration of ESFPs.…”
Section: Resultssupporting
confidence: 86%
“…After 24 h incubation, ESFP1, ESFP2 and ESFP3 displayed an appreciable effect on promoting the RAW264.7 cell proliferation ( Figure 6 a ) in a similar fashion to that reported by other researchers [21,22] . Such effect enhanced first and then reduced with increasing concentration of ESFPs.…”
Section: Resultssupporting
confidence: 86%
“…Polysaccharides from P. yezoensis have been demonstrated to have many bioactivities, including antitumor (Yu et al, 2015), hypolipidemic (Qian et al, 2014), liver protection (Guo et al, 2007), antioxidant (Isaka et al, 2015;Zhou et al, 2012) and anti-inflammatory activities (Isaka et al, 2015;Yanagido et al, 2018). Some bioassays indicated that the polysaccharide extracted from Porphyra haitanensis has immunological activity (Li et al, 2020;Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Zeng et al [ 56 ] investigated the structural characteristics of two polysaccharides obtained from Chinese water chestnut shells and showed that both had potential antioxidant activity. The low molecular weight polysaccharide extracted from Cucurbita moschata also showed proven antioxidant activity, exhibiting significant scavenging ability against ABTS and DPPH radicals [ 57 ]. Heteropolysaccharides composed of rhamnose, glucose, galactose, mannose, xylose, arabinose and galacturonic acid extracted from pistachio husk showed significant antioxidant potential [ 58 ].…”
Section: Polysaccharides From Agricultural Wastementioning
confidence: 99%
“…The high molecular weight of polysaccharides in nature makes it necessary to modify and degrade polysaccharides to improve their solubility and make them more accessible to cells [ 129 , 130 ]. Chemical [ 131 ], physical [ 80 ] and biological [ 57 , 132 ] methods are used to modify and degrade polysaccharides, thereby reducing their size and molecular weight to improve their bioactivity.…”
Section: Strategies To Increase the Biological Activitymentioning
confidence: 99%